2022
DOI: 10.3991/ijim.v16i23.36215
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things and Its Applications to Smart Campus: A Systematic Literature Review

Abstract: A smart campus is an emerging trend that will revolutionize the education system by enabling universities to improve services, and processes as well as achieve sustainability goals. With the proliferation of advanced technologies, a smart campus has emerged as an important concept that integrates technology into higher education. A smart campus takes advantage of IoT technologies to facilitate teaching and research activities. The purpose of this study is to identify the IoT technologies that are required in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In practice, ILARF can be applied to environments that require visualization using AR, IL, and data communication at the same time. Typical environments include the smart manufacturing [ 74 ], smart city [ 75 ], smart home [ 76 ], and smart campus [ 77 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, ILARF can be applied to environments that require visualization using AR, IL, and data communication at the same time. Typical environments include the smart manufacturing [ 74 ], smart city [ 75 ], smart home [ 76 ], and smart campus [ 77 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…The framework's efficiency and effectiveness were measured objectively by performance evaluation and comparison to established systems and standards. In order to analyze and interpret the research findings, a structured and data-driven method was supplied by the research design equations and variables, which included user happiness, AI model performance, optimization metrics, and smart campus adoption (Cavus et al, 2022). The user-centric design, cutting-edge technology, and data-driven decision-making that support the optimized smart campus framework promise to produce a progressive, effective, and technologically advanced learning environment that meets the various needs of all stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…The Asia-Pacific place is anticipated to develop at a charge of nearly 50% in the course of the subsequent ten years. Adopting AI's promise and making sure of its ethical use is important for progressive changes in schooling (Cavus, Mrwebi, Ibrahim, Modupeola, & Reeves, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…User-centred methodologies, such as questionnaires, interviews, and usability testing, have proven to be useful methods for evaluating user happiness, usability, and interaction effectiveness. Studies (Omitaomu & Niu, 2021;Liang & Chen, 2018;Cavus, Mrwebi, Ibrahim, Modupeola, & Reeves, 2022;Shaw, Das, Piuri, & Bianchini, 2022) have also shown the value of iterative design methods, where improvements are made as a result of ongoing user feedback, creating systems that are more streamlined and user-friendly in the end. The research on smart campuses found that while AI-based frameworks offered improved resource allocation, security management, and learning experiences, the usability component was frequently understudied (Imbar et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%